Omphalaophlebitis in A Lambs: A Case Report - Cemalettin AYVAZOĞLU; Erhan GÖKÇE; H. Metin ERDOĞAN (ISPEC Journal of Agricultural Sciences, 2020)
Umbilical lesions (omphalitis, onfalaoflebitis, omphaloarteritis, uracus fistula and hernia umbilicalis), which cause significant economic losses in ruminants, are quite common. In this study, abscess foci developed in various organs and tissues belonging to approximately 15 days old lamb that died in a sheep herd were macroscopically observed. In the necropsy evaluation, it was found that inflammation and abscess starting from the umbilical cord spread to the liver and peritoneum. According to the results of the examination, a diagnosis of onphalaophlebitis was made and the results were discussed.